Pengaruh Kompetensi Kepemimpinan Kepala Dinas Terhadap Kepuasan Pegawai Di Dinas Pariwisata, Pemuda Dan Olahraga Kabupaten Tasikmalaya - Adi Kurnia; Andi Andi (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2020)
The purpose of this research is to know, analyze and describe the satisfaction of employees about the behavior of leadership competencies from the top leaders of the organization (Head of Office) in the Tourism, Youth and Sports Agency of Tasikmalaya District. The research method used is a survey research method. The purpose of this survey is to get a picture representing that area correctly. The results of the research and analysis of statistics are obtained as follows: Recapitulation of the overall poll score about the head of Office competence in the Environment Tourism Office of Youth and Sports District Tasikmalaya is already good, a high category with a percentage of 73.19%. Recapitulation of the overall score of the employees ' work satisfaction in the Tourism Office of Youth and Sports District Tasikmalaya is already a good, high category with a percentage of 73.0%. The leadership Competence (X) has a significant effect on work satisfaction (Y) in the environment of the Youth and Sports tourism Office of Tasikmalaya Regency with a magnitude of correlation (R) of 0.873 where this figure indicates that the leadership Competence (X) has a strong relationship to work satisfaction (Y). Data analysis results, simultaneously there is a significant influence between leadership competency (X) To work satisfaction (Y) in the environment of the Youth Tourism and Sports Agency of The Tasikmalaya District.